2016
DOI: 10.1111/cen.13119
|View full text |Cite
|
Sign up to set email alerts
|

Utility of chromogranin A, pancreatic polypeptide, glucagon and gastrin in the diagnosis and follow‐up of pancreatic neuroendocrine tumours in multiple endocrine neoplasia type 1 patients

Abstract: Objective Pancreatic neuroendocrine tumors (PNETs) are the major source of disease-specific mortality in multiple endocrine neoplasia type 1 (MEN1) patients. Chromogranin A (CgA), pancreatic polypeptide (PP), glucagon, and gastrin have some diagnostic value in sporadic PNETs, but there is very little evidence for their efficacy in diagnosing PNETs in MEN1 patients. Design We performed a retrospective chart review of the existing MEN1 database in our institution. Patients One hundred thirteen patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 39 publications
0
35
0
2
Order By: Relevance
“…Two studies had maximum applicability for this review [11, 12]. de Laat et al [12] had the lowest overall risk of bias and estimated the accuracy of CgA in 81 consecutive Dutch MEN1 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies had maximum applicability for this review [11, 12]. de Laat et al [12] had the lowest overall risk of bias and estimated the accuracy of CgA in 81 consecutive Dutch MEN1 patients.…”
Section: Resultsmentioning
confidence: 99%
“…As PNETs are the most common cause of death in patients with MEN1, it is important to identify them as early as possible. We and other researchers have shown that existing circulating PNET tumour markers do not have sufficient diagnostic value in patients with MEN1 . Therefore, it is essential to identify alternative and additional risk factors for PNETs to improve early detection and potentially the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 97%
“…We and other researchers have shown that existing circulating PNET tumour markers do not have sufficient diagnostic value in patients with MEN1. 25,26 Therefore, it is essential to identify alternative and additional risk factors for PNETs to improve early detection and potentially the prognosis of these patients. In this study, we could not confirm that estrogen exposure had a protective effect against PNET risk; this was consistent with what was found in one study of pancreatic cancer, 25 although another study found the opposite result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei MEN-1-Patienten fand sich jüngst in einer großangelegten Untersuchung ein geringer Wert von CgA, PP, Glukagon und Gastrin hinsichtlich der Diagnose, Tumorgröße, Stadium, Metastasen oder Prognose eines Pankreas-NET [77].…”
Section: B Laborbefundeunclassified